Professional development is the key to securing a future rheumatology workforce. Long term evaluation of a summer school for medical students—a national scientific society’s educational initiative - Sautner, Judith; Puchner, Rudolf; Reisch, Myriam; Alkin, Alois; Duftner, Christina; Dejaco, Christian (Frontiers in Medicine, 2024)
Objectives A cumulative imbalance between rheumatologic need and an inadequate number of young colleagues entering the field leads to a dearth of rheumatologists in the near future. The Austrian Society for Rheumatology and Rehabilitation (ÖGR) has been organizing an annual Rheumatology Summer School (RSS) for medical students since 2017. The aim of this study was to analyze the annual RSS evaluations, the RSS’ overall effects on attracting new talent into the field and the lasting promotion of rheumatology. Methods A questionnaire was distributed immediately after each RSS meeting. Additionally, we conducted an electronic survey among RSS participants (2017–2022) to assess their career development trajectories. Results From 2017–2023, a total of 220 students attended the RSS. They all completed the annual evaluation. Accordingly, students’ expectations were met in 80% (2017) to 97% (2023) of cases. The electronic survey was completed by 64/133 (48%) students; 49 (77%) indicated that the RSS had markedly increased their desire to specialize in rheumatology. Among the 36 graduates, 10 (28%) had already been working in the field of rheumatology and 6 (17%) were considering this specialty but had not decided yet. RSS attendees in their 6th study year were influenced to a greater extent by the RSS to choose rheumatology as their primary specialty than 4th or 5th year students. The participants indicated that they benefited most from the RSS in terms of knowledge gain, personal awareness of rheumatology, networking among fellow students as well as gaining access to RSS faculty. Conclusion The RSS enhanced students’ intention to choose rheumatology, particularly in those close to graduation, and led to increased awareness and deeper knowledge about rheumatology.